Pengaruh Ukuran Perusahaan, Laba Rugi Operasi, Solvabilitas, Umur Perusahaan, Klasifikasi Industri, Dan Ukuran Kap Terhadap Audit Delay - Charviena Charviena; Elis Tjhoa (Ultima Accounting : Jurnal Ilmu Akuntansi, 2016)
The objective of this study was to obtain empirical evidence about the effect of company size, profit or loss, solvability, age of company, classification of industry, and public accounting firm size towards audit delay. In this study, company size was measured by log total asset, profit or loss measured by company’s operational profit or loss, solvability measured by total debt to total asset (TDTA) ratio, age of company measured since company establishment year until year of financial statement, classification of industry measured by non financial or financial industry, public accounting firm size measured by big four or non-big four. The object of this study was the company listed in Indeks Kompas 100 between 2012- 2014, sample was selected with purposive sampling, and the statistic method used in this study was multiple regression. The result of this study was profit or loss, solvability, age of company, classification of industry, and public accounting firm size had no effect towards audit delay, while company size had significant effect towards audit delay. All independent variables had significant effect towards audit delay simultaneously. Keywords : Audit Delay, Classification of Industry, Company Age, Company Size, Profit or loss, Public Accounting Firm Size, Solvability